2015
DOI: 10.1126/scitranslmed.aab4176
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory GM-CSF–producing B cells in multiple sclerosis and B cell depletion therapy

Abstract: B cells are not limited to producing protective antibodies; they also perform additional functions relevant to both health and disease. However, the relative contribution of functionally distinct B cell subsets in human disease, the signals that regulate the balance between such subsets, and which of these subsets underlie the benefits of B cell depletion therapy (BCDT) are only partially elucidated. We describe a proinflammatory, granulocyte macrophage-colony stimulating factor (GM-CSF)-expressing human memor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
353
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 371 publications
(377 citation statements)
references
References 34 publications
17
353
0
7
Order By: Relevance
“…Recent studies also elaborated the importance of antibody-independent functions of B cells in MS. In a recent study, a subtype of memory B cells that produces the proinflammatory cytokine granulocyte macrophage colony-stimulating factor (GM-CSF) was found to be more frequent and active in the blood of MS patients compared with controls [Li et al 2015b]. These B cells were especially able to switch myeloid cells (and subsequently T cells) to a proinflammatory phenotype.…”
Section: Targeting B Cells In Relapsing-remitting Multiple Sclerosis:mentioning
confidence: 99%
“…Recent studies also elaborated the importance of antibody-independent functions of B cells in MS. In a recent study, a subtype of memory B cells that produces the proinflammatory cytokine granulocyte macrophage colony-stimulating factor (GM-CSF) was found to be more frequent and active in the blood of MS patients compared with controls [Li et al 2015b]. These B cells were especially able to switch myeloid cells (and subsequently T cells) to a proinflammatory phenotype.…”
Section: Targeting B Cells In Relapsing-remitting Multiple Sclerosis:mentioning
confidence: 99%
“…Research conducted by Egwuagu and Yu reported that B cells also contribute to the overall inflammatory milieu in MS by co-stimulating T cells to produce and release inflammatory factors and of course, by promoting the production of monoclonal immunoglobulins, whose identification in the CSF still represents one of the hallmarks of the disease [48,49]. A research group showed that B cells in the peripheral blood from MS patients exhibit higher expression levels of GM-CSF receptors compared to controls, supporting the involvement of these cells in disease pathogenesis, in addition to T cells and natural killer cells (NK), which are also augmented in MS sufferers [50,51]. Nonetheless, B cells seem to play an active part in triggering the auto-inflammatory cascades of MS by stimulating the production of IL-6, tumor necrosis factor alpha (TNFα) and interferon gamma (IFN Ɣ ) as well as by acting as APCs and promoting the production of autoantibodies [45,[49][50][51][52][53].…”
Section: Ms Pathogenesismentioning
confidence: 99%
“…As already mentioned, the subset of IL-10-producing B cells (Breg cells) seems to be reduced in number or functionally impaired in MS [155][156] 159] . Vitamin D is thought to have regulatory capacities, raising high expectations for effects on Breg cells.…”
Section: Regulatory B Cells: Immune Regulation Via Il-10 Productionmentioning
confidence: 99%
“…This balance seems to be disturbed towards more pro-inflammatory cytokines in patients with MS. Indeed, B cells from patients with RRMS, compared to healthy controls, secrete more lymphotoxin, tumour necrosis factor-α, and granulocyte-macrophage colonystimulating factor [154][155] . Also, B cells of patients with MS were less capable of producing the regulatory cytokine Interleukin-10 (IL-10) [154, 156] .…”
mentioning
confidence: 99%
See 1 more Smart Citation